Two-Spirited People and Social Work Practice: Exploring the History of Aboriginal Gender and Sexual Diversity - Alaers, Jill (Critical Social Work, 2019)
Diversity of sexual orientation appears to be universal throughout human history. This article explores gender and sexual diversity of non-Aboriginal and traditional First Nations groups in North America, and the reclamation of traditional roles and identities by contemporary two-spirits. This article argues that social workers, as well as various other human service professionals stand to improve the quality of their practice by seeking deeper understanding of sexual and gender diversity through exploration of historic First Nation traditions of two-spirit roles as well as the intersecting multiple oppressions impacting two-spirits in urban, rural and reserve locations.